Managing Conflicts with Wildlife: Living with Alligators - Holly K Ober; Harry J. Dutton; Allan R. Woodward; Lindsay J. Hord; William M. Giuliano (EDIS)
American alligators are found in only 10 states in the southeastern U.S. In most situations alligators do not harm people, but they can pose potential dangers to people in some situations. In this 3-page fact sheet, we present some facts about alligators, describe their potential threats to people and pets, and provide suggestions on how to cope with these risks. Written by Holly K. Ober, Harry J. Dutton, Allan R. Woodward, Lindsay J. Hord, and William M. Giuliano, and published by the UF Department of Wildlife Ecology and Conservation, November 2014.